Efficient modeling of organic adsorbates on oxygen-intercalated graphene on Ir(111) - Järvi Jari; Todorovic Milica; Rinke Patrick (AMER PHYSICAL SOC, 2026)
Organic charge transfer complexes (CTCs) can be grown as thin films on intercalated graphene (Gr). Deciphering their precise film morphologies requires global ab initio structure search, where configurational sampling is computationally intractable unless we reconsider the model for the complex substrate. In this study, we employ charged freestanding Gr to approximate an intercalated Gr/O/Ir(111) substrate, without altering the adsoption properties of deposited molecules. We compare different methods of charging Gr and select the most appropriate substitute model for Gr/O/Ir(111) that maintains the adsorption properties of fluorinated tetracyanoquinodimethane (F4TCNQ) and tetrathiafulvalene (TTF), prototypical electron acceptor/donor molecules in CTCs. Next, we apply our model in the Bayesian optimization structure search method and density-functional theory to identify the stable structures of F4TCNQ and TTF on supported Gr. We find that both molecules physisorb to Gr in various configurations. The narrow range of adsorption energies indicates that the molecules may diffuse easily on the surface and molecule-molecule interactions likely have a central role in film formation. Our study shows that complex intercalated substrates may be approximated with charged freestanding Gr, which can facilitate exhaustive structure search of CTCs.